Biomoc a "medikalizace" společnosti jako rysy "modernity" - Daniela Tinková (AntropoWebzin)
This paper will discuss the strategiesof the health police of Enlightenment era inBohemia and in Czech lands that aimed to protecthealth as “ Gemeinwohl “ - Public Good ,Common Good . First will be highlighted general,pervasive nature of health and policing strategiesin general, then focus on two examples (whichcan be used as models of preventive measuresagainst the spread of such exposure and diseasesthat manifest themselves clearly and necessarily“egalitarian“ character, which only ensures theirreal effi ciency): fi rst, on the reform of funeral servicesand modalities, then and the introduction ofvaccination. However, while some of the “ egalitarian“ Regulation of funeral encountered a generalor partial resistance (burials in bags in orderto accelerate decomposition , replacement of individualfamily tombs, graves , tombstones ban onplacing a fl at “ recycling “ graves after 9-10 years,etc.) gradual introduction of general vaccination(apparently due to the more immediate threat offatal disease) was despite initial misgivings andmistrust basically successful. The strategies ofbio-power and medicalization are, fi nally, demonstratedin a detail on the the phaenomenon ofthe „birth of the birth clinic“ (and, more generally,the professionalization of obstetrics in 18thcentury), that could be considered as example parexcellence.In conclusion, it should be emphasizedthat it was police- bureaucratic character of theAustrian state and its control mechanisms signifi -cantly helped to promote new health and hygienerules and health- disciplining mechanisms , whichundoubtedly contributed to the gradual improvementof the level of health in our country.